The Relationship between Multiple Intelligences of Preservice Elementary Teacher toward Their Gender and Performances - Muhammad Ikhlas; Kuswanto Kuswanto; Rosario F. Quicho (Universitas Muhammadiyah Surakarta, 2021)
This research studies whether there is a significant relationship between the multiple intelligences of pre-service elementary teachers, their gender, and their performances. The survey method has been used for this study. A “Multiple Intelligence Profiling Questionnaire III (MIPQ-III)” was used to collect the multiple intelligences of the participants. Reliability-test has been used to see the consistency of the questionnaire. In order to analysis of the data, descriptive statistics, independent sample t-test, and Pearson correlation were used for this study. Results showed that naturalistic intelligence has the highest mean score. Meanwhile, logical-mathematics intelligence has the lowest mean score. Results also showed that logical-mathematic, verbal-linguistic, spatial, bodily-kinesthetics, and interpersonal intelligence have differences based on gender, while other intelligence has no differences. Furthermore, results also show that all intelligence, excluding naturalistic, positively correlates with the performances. Lastly, hierarchical regression shows that among the multiple intelligences, the logical-mathematics intelligence becomes a predictor for the performance of the pre-service elementary teachers. The implications of this study, such as the results, show a relationship between multiple intelligence and elementary school pre-service teachers. Besides that, it is found that the multiple intelligence of elementary pre-service teachers has a wide variety of impacts on the performance of those pre-service teachers in the future. Thus, it is expected that relevant stakeholders can better review these aspects, especially in the curriculum